Paolo Mascagni and Alessandro Moreschi: the intellectual property right on the discovery of the vascular structure of urethral tissue - Armocida, Emanuele; Natale, Gianfranco (Italian Journal of Anatomy and Embryology, 2018)
In the beginning of the XIX century, when both vascular and cellular texture theories con- cerning the penis structure were still coexisting, three figures were involved in the controver- sy about the priority of the discovery of the vascular nature of human erectile tissues: Paolo Mascagni (1755-1815), represented by his pupil Tommaso Farnese (1780-1829), and Alessandro Moreschi (1771-1826). In the Elogio del celebre anatomico Paolo Mascagni (1816), Farnese attrib- uted to his mentor the demonstration in 1809 of the continuity between arteries and veins and the description of venous plexuses, this term replacing the previous and misleading name of spongy body attributed to the inner part of penis. But in 1817 Moreschi inflamed the dispute, claiming for the priority of that discovery, with the publication of his anatomical work and a polemical essay against Farnese [1]. Farnese promptly replied with Note addizionali del Dot- tore Tommaso Farnese al suo elogio di Paolo Mascagni (1818) [2], where he reported a meeting with Moreschi in Bologna in 1810. In that occasion, Farnese explained a Mascagni’s technique to perfuse urethral blood vessels that Moreschi would have plagiarized. Furthermore, Farnese also included eight testimonies claiming to have seen Mascagni performing such injections before 1810. The Prodromo della grande anatomia, a posthumous work of Mascagni edited in1819, includes a plate dedicated to the structure of the urethra and a comprehensive view of this scientific story. In short, Mascagni developed a technique to inject urethral blood vessels, but Moreschi was the first to publish an accurate work on this subject. For this reason, many Italian and international authors have attributed to the latter the discovery of the venous circu- lation of the urethra.